2021
DOI: 10.2196/20046
|View full text |Cite
|
Sign up to set email alerts
|

Views on Using Social Robots in Professional Caregiving: Content Analysis of a Scenario Method Workshop

Abstract: Background Interest in digital technologies in the health care sector is growing and can be a way to reduce the burden on professional caregivers while helping people to become more independent. Social robots are regarded as a special form of technology that can be usefully applied in professional caregiving with the potential to focus on interpersonal contact. While implementation is progressing slowly, a debate on the concepts and applications of social robots in future care is … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0
3

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 36 publications
0
6
0
3
Order By: Relevance
“…Similar studies have concentrated the objective of their analysis on the perception of technologies or robots in samples of health professionals and patients, both potential end users of these devices [ 20 , 21 , 22 , 23 , 24 , 25 , 26 , 27 , 28 , 37 , 38 , 39 , 40 ].…”
Section: Discussionmentioning
confidence: 99%
“…Similar studies have concentrated the objective of their analysis on the perception of technologies or robots in samples of health professionals and patients, both potential end users of these devices [ 20 , 21 , 22 , 23 , 24 , 25 , 26 , 27 , 28 , 37 , 38 , 39 , 40 ].…”
Section: Discussionmentioning
confidence: 99%
“…Daher passt die Aufgliederung von Busse et al. ( 2021 ), in der ein Serviceroboter zu den sozialen Robotern gehört, sehr gut zu den Vorstellungen der Teilnehmenden. Es hebt hervor, dass die zukünftige Roboterentwicklung sich nicht zu starr auf die Trennung von sozialen Robotern und Servicerobotern fokussieren sollte, sondern die optimale Abstimmung zwischen funktionalen und sozialen Funktionen gesucht werden soll.…”
Section: Diskussionunclassified
“…Eine der grössten Stärken dieses Projektes war, dass die Perspektiven von potenziellen Anwenderinnen und Anwendern von sozialen Robotern im Gesundheitsbereich in der Schweiz untersucht wurden, wodurch die Evidenz für Robotereinsätze im Schweizerischen Gesundheitsbereich zu den Ergebnissen von Busse et al. ( 2021 ) erweitert wurde. Zudem war es wichtig, dass nicht nur eine Berufsgruppe (z.…”
Section: Diskussionunclassified
See 1 more Smart Citation
“…According to reinforcement theory, when individuals observed that pleasurable consequences would follow, they are more likely to engage in a behavior [ 24 ]. As robots have only relatively recently been introduced into nurses’ workplaces [ 25 ], we may expect that a positive attitude toward robots would also motivate nurses’ engagement. Hence, we hypothesized that a positive attitude toward robots is positively related to nurse–robot engagement (H5).…”
Section: Introductionmentioning
confidence: 99%